Bitmoji Application and Young Learners Creativity in Learning English Vocabulary The Research conducted to 7th Grade Student of SMP Negeri 1 Kauditan - Sulfany Tineh (English Education Postgraduate Program, Universitas Negeri Manado, 2023)
For teaching and learning process today especially since the Covid 19 teachers rely more on technology as a medium or learning tool One of the main problems that arise in learning English as a foreign language or second language for the young learners is vocabulary Besides in the area of research English is taught in not all primary schools So it becomes hard for the students to learn English when they come to Junior High School The lack of vocabulary of the 7th < sup>grade student of SMP Negeri 1 Kauditan is the reason for the writer to raise vocabulary as a problem for the young learners that must be found a way out For this reason Bitmoji Application are used in this study to be used as interactive and interesting learning media for young learners so it is hoped that it will help them master vocabulary more quickly and easily In this study 30 students of 7th< sup> grade of SMP Negeri 1 Kauditan were the participants This is qualitative research and the results of this study are expected to help teachers in the classroom in teaching vocabulary < p>